Epidemiology of Acute Kidney Injury in Critically Ill Children and Young Adults - Kaddourah, Ahmad; Basu, Rajit K; Bagshaw, Sean M; Goldstein, Stuart L (The New England journal of medicine, 2017)
Most children with serious acute illness do not have underlying chronic conditions. This prospective study involving patients in pediatric intensive care units showed that acute kidney injury is common and is associated with poor outcomes, including increased mortality. Epidemiologic studies involving adults have shown that acute kidney injury is associated with increased mortality, prolonged mechanical ventilation, and prolonged length of stay in intensive care units (ICUs). 1 – 3 A multinational, prospective study involving 1802 adults 3 initiated the use of Kidney Disease: Improving Global Outcomes (KDIGO) guidelines to describe the epidemiology of acute kidney injury; the guidelines 4 define and stage acute kidney injury according to the plasma creatinine level and urine output (Table S1 in the Supplementary Appendix, available with the full text of this article at NEJM.org). That study showed graded associations between the severity of acute kidney injury and . . .